Female Sex Worker Social Networks and STI/HIV Prevention in South China - Tucker, Joseph D. (Public Library of Science, 2011)
BACKGROUND: Reducing harm associated with selling and purchasing sex is an important public health priority in China, yet there are few examples of sustainable, successful programs to promote sexual health among female sex workers. The limited civil society and scope of nongovernmental organizations circumscribe the local capacity of female sex workers to collectively organize, advocate for their rights, and implement STI/HIV prevention programs. The purpose of this study was to examine social networks among low-income female sex workers in South China to determine their potential for sexual health promotion. METHODS/PRINCIPAL FINDINGS: Semi-structured interviews with 34 low-income female sex workers and 28 health outreach members were used to examine how social relationships affected condom use and negotiation, STI/HIV testing and health-seeking behaviors, and dealing with violent clients. These data suggested that sex worker's laoxiang (hometown social connections) were more powerful than relationships between women selling sex at the same venue in establishing the terms and risk of commercial sex. Female sex workers from the same hometown often migrated to the city with their laoxiang and these social connections fulfilled many of the functions of nongovernmental organizations, including collective mobilization, condom promotion, violence mitigation, and promotion of health-seeking behaviors. Outreach members observed that sex workers accompanied by their laoxiang were often more willing to accept STI/HIV testing and trust local sexual health services. CONCLUSIONS/SIGNIFICANCE: Organizing STI/HIV prevention services around an explicitly defined laoxiang social network may provide a strong foundation for sex worker health programs. Further research on dyadic interpersonal relationships between female sex workers, group dynamics and norm establishment, and the social network characteristics are needed.